2018
DOI: 10.1371/journal.pgen.1007355
|View full text |Cite
|
Sign up to set email alerts
|

Targeted next generation sequencing identifies functionally deleterious germline mutations in novel genes in early-onset/familial prostate cancer

Abstract: Considering that mutations in known prostate cancer (PrCa) predisposition genes, including those responsible for hereditary breast/ovarian cancer and Lynch syndromes, explain less than 5% of early-onset/familial PrCa, we have sequenced 94 genes associated with cancer predisposition using next generation sequencing (NGS) in a series of 121 PrCa patients. We found monoallelic truncating/functionally deleterious mutations in seven genes, including ATM and CHEK2, which have previously been associated with PrCa pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 77 publications
6
78
0
Order By: Relevance
“…CHEK2 variants have been associated with PrCa predisposition in several studies [9,10], and we found that this gene was the most frequently mutated Tier 1 gene in our study (4.1%). In a recent study of 217 metastatic PrCa patients from Sweden [31], CHEK2 was also the most frequently mutated DNA repair gene (3.8%), highlighting the importance of CHEK2 mutations for aggressive PrCa in the Nordic population.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…CHEK2 variants have been associated with PrCa predisposition in several studies [9,10], and we found that this gene was the most frequently mutated Tier 1 gene in our study (4.1%). In a recent study of 217 metastatic PrCa patients from Sweden [31], CHEK2 was also the most frequently mutated DNA repair gene (3.8%), highlighting the importance of CHEK2 mutations for aggressive PrCa in the Nordic population.…”
Section: Discussionsupporting
confidence: 70%
“…ATM and its role in pancreatic cancer was recently reviewed [35] and germline mutations in ATM have been associated with predisposition for several cancer forms [36] including PrCa [3]. Several studies have particularly reported potentially damaging variants in ATM in aggressive PrCa cases [7,9,29,31]. We also found high frequencies of potentially damaging variants in our lethal cohort (3.28% and 1.64% for Tier 1 and 2 variants, respectively), while in the unselected cases, the frequencies of these variants were found to be very low, similar to those of the population controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cep57 insufficiency could drive tumorigenesis in this way. Interestingly, CEP57 insufficiency correlates with tumor growth and metastasis in 2 prostate cancer patient cohorts, and monoallelic mutation was reported in early-onset familial prostate cancers ( 58 , 59 ). Irrespective of the exact mechanism of tumorigenesis, the currently available data warrant future investigations as to whether homozygous and heterozygous carriers of inactivating CEP57 mutations would benefit from intensified cancer screenings, for instance by the use of newly developed multianalyte blood tests ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides RTS patients with RECQL4 mutations, our proposed regimen maybe used for cancer patients with germline RECLQ4 mutations. For instance, recent studies reveal that a small fraction of cancer patients also have RECQL4 mutations, 55,56 and we expect that our study may partially help with the genomic diagnosis for cancer treatment in the future. RTS patients are at high risk for OS at young ages without affecting prognosis significantly.…”
Section: Discussionmentioning
confidence: 87%